2016
DOI: 10.1002/2016gc006521
|View full text |Cite
|
Sign up to set email alerts
|

Synchrotron X-ray computed microtomography study on gas hydrate decomposition in a sedimentary matrix

Abstract: In-situ synchrotron X-ray computed microtomography with sub-micrometer voxel size was used to study the decomposition of gas hydrates in a sedimentary matrix. Xenon-hydrate was used instead of methane hydrate to enhance the absorption contrast. The microstructural features of the decomposition process were elucidated indicating that the decomposition starts at the hydrate-gas interface; it does not proceed at the contacts with quartz grains. Melt water accumulates at retreating hydrate surface. The decompositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
114
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 205 publications
(120 citation statements)
references
References 91 publications
6
114
0
Order By: Relevance
“…X‐ray computed tomography (CT) enables nondestructive 3‐D visualization of hydrate‐bearing sediments and is increasingly applied in the hydrate field to understand interactions between hydrate and surrounding sediments (Chaouachi et al, ; Chen & Espinoza, ; Choi et al, ; Jin et al, ; Seol & Kneafsey, ; Ta et al, ; Yang et al, ). However, methane hydrate segmentation from the surrounding pore liquid is difficult as the attenuation coefficient of methane hydrate is close to that of water.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…X‐ray computed tomography (CT) enables nondestructive 3‐D visualization of hydrate‐bearing sediments and is increasingly applied in the hydrate field to understand interactions between hydrate and surrounding sediments (Chaouachi et al, ; Chen & Espinoza, ; Choi et al, ; Jin et al, ; Seol & Kneafsey, ; Ta et al, ; Yang et al, ). However, methane hydrate segmentation from the surrounding pore liquid is difficult as the attenuation coefficient of methane hydrate is close to that of water.…”
Section: Introductionmentioning
confidence: 99%
“…Proper interpretation and utilization of these results heavily rely on understanding the pore habits of methane hydrate, which to date have only been indirectly determined with acoustic velocity measurements (Santamarina et al, 2015). X-ray computed tomography (CT) enables nondestructive 3-D visualization of hydrate-bearing sediments and is increasingly applied in the hydrate field to understand interactions between hydrate and surrounding sediments (Chaouachi et al, 2015;Chen & Espinoza, 2018;Choi et al, 2011;Jin et al, 2008;Seol & Kneafsey, 2009;Ta et al, 2015;Yang et al, 2016). However, methane hydrate segmentation from the surrounding pore liquid is difficult as the attenuation coefficient of methane hydrate is close to that of water.…”
Section: Introductionmentioning
confidence: 99%
“…One of the possible explanations is that the intrinsic strength of methane hydrate is 20 to 30 times stronger than that of ice at a temperature near the freezing point (Durham, 2003). Moreover, water films between hydrate crusts or crystals and grain surfaces (Chaouachi et al, 2015;Yang et al, 2016), unfrozen water (Chamberlain et al, Figure 7. The determined shear strength shows the effect of hydrate bearing and freezing on shear strength.…”
Section: Physical Model Of Hydrate Reinforcement Of Sedimentsmentioning
confidence: 99%
“…Other compounds such as tetrahydrofuran (THF), carbon dioxide (CO 2 ), and xenon (Xe) can also form hydrates in the presence of water, and laboratory experiments often resort to these hydrate formers as alternatives to methane in order to recreate and understand hydrate phenomena in nature. Among these three most common analogs to methane hydrate, xenon hydrate has become increasingly popular as an experimental analog in recent years (Chaouachi et al, , ; Chen & Espinoza, ; Chen et al, ; Jin et al, ; Waite et al, ; Yang et al, ). There are four main reasons for this: (1) Xenon forms structure I hydrate up to 1.8 GPa (Sanloup et al, ), which is the hydrate structure commonly observed in nature; (2) xenon remains a gas phase under relevant experimental conditions (in contrast to THF, which is a liquid that is fully miscible with water and therefore poorly suited for studies of interfacial growth and multiphase dissociation of hydrate); (3) xenon is nonflammable and can be used to form hydrates under ambient temperature and moderate pressure (e.g., 24 °C and 7 MPa), experimental conditions which are easier to create and control in the laboratory relative to what is required for methane hydrate; and (4) due to its high molecular mass (131.3 g/mol), xenon gas can enhance the density contrast between gas hydrate and the aqueous solution, thus significantly improving image quality when using X‐ray computed tomography (CT).…”
Section: Introductionmentioning
confidence: 99%